Spider-Ham. A pig in time - Foxe, Steve; Amin, Shadia (New York, NY : Graphix, an imprint of Scholastic, 2024)
It's just a normal day in the life of Peter Porker, your friendly neighborhood Spider-Ham! Keeping New Yolk City safe from dastardly villains is no easy feat, especially when the Green Gobbler from the year 2099 travels back in time to team up with his present-day counterpart. Talk about a pair of rotten eggs! What's worse, Spider-Ham gets flung into the future, making it impossible to stop the duo's evil plot. He'll have to team up with heroes from all across time if he wants to make it back and save the day.
K-3
GN520L
Keywords: Spider-Ham -- (Fictitious character) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Superheroes -- Juvenile fiction; Swine -- Comic books, strips, etc; Swine -- Juvenile fiction; Animals -- Comic books, strips, etc; Animals -- Juvenile fiction; Time travel -- Comic books, strips, etc; Time travel -- Juvenile fiction; Spider-Ham -- (Fictitious character) -- Fiction; Superheroes -- Fiction; Pigs -- Fiction; Animals -- Fiction; Time travel -- Fiction; Time-travel comics; Superhero comics; Comics (Graphic works); Humorous comics; Graphic novels